Discrepancies between Multi-Electrode LFP and CSD Phase-Patterns: A Forward Modeling Study - Hindriks, Rikkert; Arsiwalla, Xerxes D.; Panagiotaropoulos, Theofanis; Besserve, Michel; Verschure, Paul F. M. J.; Logothetis, Nikos K.; Deco, Gustavo (Frontiers in Neural Circuits, 2016)
Multi-electrode recordings of local field potentials (LFP's) provide the opportunity to investigate the spatiotemporal organization of neural activity on the scale of several millimeters. In particular, the phases of oscillatory LFP's allow studying the coordination of neural oscillations in time and space and to tie it to cognitive processing. Given the computational roles of LFP phases, it is important to know how they relate to the phases of the underlying current source densities (CSD's) that generate them. Although CSD's and LFP's are distinct physical quantities, they are often (implicitly) identified when interpreting experimental observations.That this identification is problematic is clear from the fact that LFP phases change when switching to different electrode montages, while the underlying CSD phases remain unchanged. In this study we use a volume-conductor model to characterize discrepancies between LFP and CSD phase-patterns, to identify the contributing factors, and to assess the effect of different electrode montages. Although we focus on cortical LFP's recorded with two-dimensional (Utah) arrays, our findings are also relevant for other electrode configurations. We found that the main factors that determine the discrepancy between CSD and LFP phase-patterns are the frequency of the neural oscillations and the extent to which the laminar CSD profile is balanced. Furthermore, the presence of laminar phase-differences in cortical oscillations, as commonly observed in experiments, precludes identifying LFP phases with those of the oscillations at a given cortical depth. This observation potentially complicates the interpretation of spike-LFP coherence and spike-triggered CSD averages. With respect to reference strategies, we found that the average-reference montage leads to larger discrepancies between LFP and CSD phases as compared with the referential montage, while the Laplacian montage reduces these discrepancies.